2020
DOI: 10.1177/0363546520966624
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Anatomic Anterior Cruciate Ligament Reconstruction With Lateral Extra-articular Tenodesis Does Not Significantly Affect Rotatory Knee Laxity: A Time Zero, In Vivo Kinematic Analysis

Abstract: Background: The pivot-shift test is used to assess for rotatory knee laxity in the anterior cruciate ligament (ACL)-deficient knee and ACL-reconstructed knee; however, the pivot shift uses a subjective grading system that is limited by variability between examiners. Consequently, quantified pivot shift (QPS) test software (PIVOT iPad application) has been developed and validated to measure the magnitude of rotatory knee laxity during the positive pivot-shift test. Purpose: To employ intraoperative QPS (iQPS) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…7 Recent systematic reviews and meta-analyses have shown that anterolateral surgical interventions are generally effective in rotatory constraint and reduce graft failure. 2,23 For the current study, after ACLR, all grade 3 positive pivot shift signs detected before surgery had turned negative at the 1-year follow-up with or without ALSA, agreeing with the study of Sheean et al 10 Similarly, no significant difference in medialelateral compartmental sliding distances were found (Table 3). Therefore, these data demonstrated that the isolated DB-ACLR can be a good solution for those patients with a high-grade pivot-shift.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…7 Recent systematic reviews and meta-analyses have shown that anterolateral surgical interventions are generally effective in rotatory constraint and reduce graft failure. 2,23 For the current study, after ACLR, all grade 3 positive pivot shift signs detected before surgery had turned negative at the 1-year follow-up with or without ALSA, agreeing with the study of Sheean et al 10 Similarly, no significant difference in medialelateral compartmental sliding distances were found (Table 3). Therefore, these data demonstrated that the isolated DB-ACLR can be a good solution for those patients with a high-grade pivot-shift.…”
Section: Discussionsupporting
confidence: 91%
“…7 Some researchers reported promising clinical outcomes, as decreased ACL-graft ruptures 8 and better survival of meniscal repair 9 were observed in the combined ACLR with ALSA knees. However, others found no benefit on the rotatory control 10 or even overconstrained knee motion 11 after the procedure.…”
Section: See Commentary On Page 1237mentioning
confidence: 99%
“…Biomechanical, cadaveric, and clinical studies have investigated the advantages, disadvantages, and clinical results of these combined procedures [27, 31, 40, 47]. Some studies have analyzed the kinematic effect of lateral extra‐articular tenodesis (LET) in vivo [6, 34, 42, 49]. All those investigations were carried out with a focus on the effects of the combined LET and ACL procedures and described contrary results.…”
Section: Introductionmentioning
confidence: 99%
“…17 A time-zero, in vivo kinematic analysis using quantified pivot-shift test software showed that both ACL reconstruction and ACL reconstruction augmented with LET resulted in significant decreases in rotatory knee laxity and that the augmentation of ACL reconstruction with LET did not change the constraint of the knee with respect to lateral compartment translation, suggesting that the utility of combining LET with ACL reconstruction remains unclear and future research is necessary to refine the indications for LET in patients determined to be at risk for residual rotatory knee instability and/or variations in injury pattern. 41…”
Section: Discussionmentioning
confidence: 99%
“…17 A time-zero, in vivo kinematic analysis using quantified pivot-shift test software showed that both ACL reconstruction and ACL reconstruction augmented with LET resulted in significant decreases in rotatory knee laxity and that the augmentation of ACL reconstruction with LET did not change the constraint of the knee with respect to lateral compartment translation, suggesting that the utility of combining LET with ACL reconstruction remains unclear and future research is necessary to refine the indications for LET in patients determined to be at risk for residual rotatory knee instability and/or variations in injury pattern. 41 Among 5 studies included in the current review, 4 studies directly compared outcomes between a group with unrepaired Segond fracture and a group with no Segond fracture. Interestingly, the current meta-analysis of those 4 studies (292 patients with Segond fracture and 2114 without Segond fracture) showed no statistically significant difference in the risk of graft failure or revision surgery between the group with unrepaired Segond fracture and the group with no Segond fracture.…”
Section: Discussionmentioning
confidence: 99%